Hegemony Among Characters in `Bekisar Merah` Novel By Ahmad Tohary - Rangga Agnibaya; Suyitno Suyitno; Herman J. Waluyo (Universitas Muhammadiyah Semarang, 2018)
The correlation between literature and reality is very close. This situation cannot be separated from the fact that literature figures as literature producers live in middle of society with various problems. BekisarMerah, a novel by Ahmad Tohari is a literature close to society fact. One of the fact is the interaction among characters which represented the real situation in the society. The interaction patterns which were formed in Bekisar Merah have their own unique characteristics, depending on who are having the interaction. Using the Socio-Literature approach and Hegemony concept by Antonio Gramsci, this article tries to discuss and analyze the interaction happened among characters, especially those which resulted in the existence of social inequality. Furthermore, this article means to analyze and discuss the pattern of relationship among characters in the Bekisar Merah Novel.